Peningkatan Motorik Kasar Melalui Pembelajaran Daring Berbasis Whats App - Andini, Diah Puspita; Marlinah, Marlinah; Nurchahyani, Nurchahyani; Apriyanti, Sesiyana; Silaban, Esnirani; Yuliantina, Irma (Universitas Nusantara PGRI Kediri, 2021)
Improving learning through rough motoric activities using WhatsApp application at RA Al Muttaqin. This research was implemented using offline (Visit School) and online (WhatsApp applications) methods as a problem solver for teaching and learning activities (KBM) at RA Al Muttaqin during the Covid-19 pandemic. Based on the results of motoric physical activity through WhatsApp learning was applied by making video of learning to know children’s rough motoric development. Generally, WhatsApp-based online learning challenges teacher’s creativity, in planning fun and interesting learning programs by developing collaboration between teachers, parents and participants, that is become the best solution in the Covid-19 pandemic that demands to take care of the physical.